A technique to control major hazards of the coal gasification process developed from critical events and safety barriers. Issue 4 (6th February 2017) - Sun, Feng; Xu, Wei; Wang, Guangjian; Sun, Bing
Abstract : Many coal gasification related accidents happened in China recently. Investigations of the accidents show that the performance of safety barriers and the risk influence factors contributing to it plays an important role. Lack of attention on the performance of safety barriers and associated risk influence factors hinder the thorough understanding of these accidents and, therefore, needs to be addressed by providing a new analysis methodology. Herein, we developed an approach from critical events and safety barriers to control the major hazards during the coal gasification process. The method consists of process hazard identification based on critical events, barrier performance evaluation based on barrier diagrams, and quantification of risk influence factors based on Bayesian network. The application of the method indicates that it is suitable for controlling major hazards of the coal gasification process as well as other chemical processes. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 382–391, 2017